2013
DOI: 10.1016/j.jcmg.2012.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Monitoring of Oxidative Stress in Transplanted Mesenchymal Stromal Cells

Abstract: Objectives We aimed to validate a pathway-specific reporter gene that could be used to noninvasively image the oxidative status of progenitor cells. Background In cell therapy studies, reporter gene imaging plays a valuable role in the assessment of cell fate in living subjects. After myocardial injury, noxious stimuli in the host tissue confer oxidative stress to transplanted cells that may influence their survival and reparative function. Methods Rat mesenchymal stromal cells (MSCs) were studied for phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Moreover, staining histological sections with annexin V also got a consistent result [28]. Meanwhile, other targets, including 64 Cu-TNP [29], MPO(Gd) [30], 123 I-BMIPP [31], 111 I-VEGF 121 [32], EP-2104R [33], have been used to assess angiogenesis processes in atherosclerosis by established radiotracers.…”
Section: Atherosclerosismentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, staining histological sections with annexin V also got a consistent result [28]. Meanwhile, other targets, including 64 Cu-TNP [29], MPO(Gd) [30], 123 I-BMIPP [31], 111 I-VEGF 121 [32], EP-2104R [33], have been used to assess angiogenesis processes in atherosclerosis by established radiotracers.…”
Section: Atherosclerosismentioning
confidence: 88%
“…The conditions of some molecules can reflect the state of disease progression after stem cells delivery. For instance, reporter gene imaging allows assessment of changes in the oxidative status of mesenchymal stem cells (MSCs) after delivery to ischemic myocardium in a rat model of myocardial ischemia/reperfusion [64]. So imaging of these molecules, such as imaging of integrin a v b 3, exposed phosphatidylserine, glucose metabolism and extracellular matrix remodeling, provides a better understanding of molecular changes after stem cells therapy (Fig.…”
Section: Molecular Imaging Therapeutic Effects Of Stem Cellsmentioning
confidence: 99%
“…To evaluate the oxidative stress in tissues, test animals were euthanized on the first day following treatment, and their quadriceps muscles were harvested and processed for immunostaining. Tissue sections were separately incubated with primary antibodies against oxidative-damage markers 8-hydroxy-2'-deoxyguanosine (8-OHdG; JaICA, Shizuoka, Japan) and 4-hydroxynonenal (4-HNE) [31,32], visualized by fluorophore-conjugated secondary antibodies (Life Technologies), counterstained with DAPI, and then observed using a CLSM.…”
Section: Evaluation Of Oxidative Stress In Ischemic Limbsmentioning
confidence: 99%
“…In fact, bioluminescence imaging (BLI) has been used to study the kinetics of the viability of myocardial-implanted cells in living animals [27]. Furthermore, we recently reported that reporter gene imaging can also be used to monitor specific biological processes using conditional transgenes whose expression is regulated by pathway-specific promoters [32]. …”
Section: Introductionmentioning
confidence: 99%